Investigation on ideal mechanical performance of laser direct energy deposited Ti–6Al–2Zr–1Mo–1V alloy without sub-β transus thermal cycles. (September 2022) - Li, Renkai; He, Bei; Wang, Huaming
Abstract: One goal of metal additive manufacturing is to fabricate high-performance components without post processing. However, the last several deposited layers of as-deposited parts do not experience sub-β transus thermal cycles, resulting in slight differences in microstructure and mechanical properties from other deposited layers. Finer α lath in titanium alloys generally gives increased strength and decreased ductility, while in this study, although laser direct energy deposited Ti–6Al–2Zr–1Mo–1V alloy without sub-β transus thermal cycles exhibited finer α laths, it exhibited higher strength (921.0 ± 1.0 MPa) and similar ductility (9.2 ± 2.1%) compared to that with sub-β transus thermal cycles (898.3 ± 4.0 MPa/8.8 ± 1.3%). The ideal ductility was mainly attributed to the enhanced stain hardening ability. This study indicated that the laser direct energy deposited parts had ideal mechanical properties in the as deposited state. Highlights: The last five deposited layers experienced no sub-β transus thermal cycles. The layers without sub-β transus thermal cycles showed finer α lamellae compared with the other layers. The layers without sub-β transus thermal cycles exhibited higher strength and comparable ductility.